Who is protected and who is not? Evaluating the effects of the long-term care insurance system and disparities in healthcare utilization and costs of the South Korean elderly population - Minsung Sohn; Hojoon Sohn; Mankyu Choi (BMC Health Services Research)
Abstract Background There is a growing global interest in investigating the substitutability between long-term care service (LTCS) and medical care use, particularly in countries where elderly medical care use is rapidly increasing. The use of an appropriate LTCS can reduce unnecessary medical utilization and the resulting costs such as those for hospital admission, delayed discharge, and emergency room visits. Methods This study evaluated whether the LTCS has a savings effect on medical use for older adults and whether the effect varies depending on income level, using longitudinal data obtained from an Elderly Cohort Database compiled from 2002 to 2013, which is a sample of 10% of the elderly population in Korea. This study also included 70,437 older adults who participated during the 2002–2007 (pre-policy) and 2009–2013 (post-policy) periods. Results The results show that the use of inpatient and long-term care hospitals decreased significantly in LTCS users compared with non-users; additionally, the length of stay and medical costs were lower. However, since the introduction of the system, the use of outpatient and acute care hospitals (ACH) by LTCS users has increased slightly compared with non-users. Low-income LTCS users experienced more cost-sharing in outpatient and ACH than high-income users. Conclusions Although LTCI system could reduce the hospitalization rate for the older adults using LTCS, more attention to middle- and low-income populations is necessary as they may be within the blind spot of security.